Glycation, oxidation and glycoxidation of IgG: a biophysical, biochemical, immunological and hematological study. Issue 10 (27th July 2018) - Islam, Sidra; Moinuddin,; Mir, Abdul Rouf; Raghav, Alok; Habib, Safia; Alam, Khursheed; Ali, Asif
Abstract : Glycation and oxidation induce structural alterations in the proteins in an interdependent manner with consequent pathological implications. The published literature presents wide range of modifications in conformational characteristics of proteins by glycation and oxidation; however, there is little data that could elaborate the cumulative effect of both the processes. This study has analysed the modifications in IgG by methylglyoxal (MG) (glycative stress), hydroxyl radical ( ) (oxidative stress) and by their combined action i.e. treatment of MG glycated IgG (glycoxidation). It further addresses the implications of the altered structural integrity of IgG on its immunological characteristics and impact on haematological parameters in rabbits. Using circular dichroism, FTIR, SDS-PAGE analysis, thioflavin-T fluorescence assay, congo red absorbance analysis, dynamic light scattering, transmission electron microscopy, ELISA, blood cell counts and rectal temperature studies, we report that the glycoxidative modification caused maximum alteration in the IgG as compared to the glycatively and oxidatively modified protein. Far-UV CD results confirmed the highest decline in the beta-pleated sheet content of the protein by glycoxidation. The damage led to the reduced flexibility and enhanced electronic interactions in IgG as observed by near-UV CD. Modifications caused cross-linking and adduct formation in the serum protein. The electron micrograph confirmed amorphous aggregation in modified IgG. The modifications increased the hydrodynamic radius of IgG by allowing the attachment of and MG residues. The glycoxidatively modified IgG induced the maximum antibody titres that showed high specificity towards the altered IgG. The glycoxidation of IgG leads to activation of inflammatory pathways.